Historical Analysis of Mangrove Ecosystems Changes in Tidal Disasters-Prone Areas Using Remote Sensing - Putri, Adhe Viana Yulida; Sadono, Ronggo; Poedjirahajoe, Erny (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Mangrove ecosystems are vital for human livelihoods, but ongoing exploitation and natural disturbances have led to significant land use and cover changes. Therefore, this study aimed to identify trends regarding land cover (LC) changes in mangrove ecosystems using remote sensing. LC changes from 1988 to 2024, as observed using remote sensing techniques. Satellite imagery from Landsat 5 TM, Landsat 7 ETM+, Landsat 8 OLI/TRIS, and Landsat 9 OLI/TRIS was analyzed using the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and a newly developed Combined Mangrove Recognition Index (CMRI). The results revealed four distinct phases of LC change over the study period (1988–2024), starting from 1988 to 1989, during which 12.14 ha of mangrove forest were documented. The second phase, spanning from 1990 to 1994, witnessed the onset of anthropogenic disturbances in pond area expansion, totaling 41.04 ha. The third phase, which spanned from 1995 to 1998, featured abrasion, resulting in 11.56 ha reduction in the area covered. Natural ecosystem recovery began in 1998 and continued with human intervention in the fourth phase from 2008 to 2024, resulting in an increase in mangrove forest LC by 62.57 ha. The study demonstrates the utility of remote sensing in documenting ecological changes over time and provides critical insights for sustainable coastal management and policymaking in vulnerable urban coastal zones.